The Influence Ethics on Corporate Crime Within The Scope Business Crime - Novi Juli Rosani Zulkarnain (LEGAL BRIEF, 2021)
The Influence of Business Ethics on Corporate Crime in the Scope of Business Crime". The corporate sector that is able to play a positive role in national development is the corporate sector which is a national asset and not a corporation which is only a burden and a parasite of society. This corporate sector group is a group that complies with business ethics, for example, adheres to good corporate governance, obeys the rules of the game of healthy business competition, and applicable laws and regulations. In other words, this positive role in national development refers to corporations that are able to practice the principles of business ethics and also the principles of good corporate governance in carrying out their business activities.There is a tendency to punish corporations more using the "Subsidiarity" principle, namely criminal law is placed in the position of"Ultimate Remedium". However, as an effort for the Deterrence Effect, for the punishment of corporations, it is possible to place criminal law as "PrimumRemedium", because corporate crimes can damage the joints of economic life and endanger the survival of a nation.